ANALISIS KETERLIBATAN APARATUR SIPIL NEGARA DALAM PROSES PEMILIHAN UMUM TAHUN 2019 KABUPATEN TAPANULI UTARA - SILABAN, CHARLES ROMUAL; MANALU, DIMPOS; SINAGA, BUDIMAN NPD (LP2MTBM MAKARIOZ, 2022)
The bureaucracy and polithics are very difficult to divide when civil personnel, the state has engaged itself in activism, the practical politics of politicians, both at the level, in dacrah and at the level, center, this research will want to revisit the involvement of state civil personnel in the 2019 district of Northern Tapanuli. This research is about to control how to reconcile the state's civil-personnel involvement in the box Legislative 2019 in the Northern Tapanuli district, as well as to know, what are the factors.The involvement of the civil personnel, the country in the practical political activities at Legislative Elections This research, using qualitative methods, with data collection technologies done through studies, libraries and interviews with the relevant parties. The data collected is then analyzed using bureaucratic politicization, bureaucratic political control theory, and bureaucratic neutrality theories to narrow out the involvement of state civil personnel in practical political acumen. Based on the research that's been done, In the process of holding the 2019 Legislative Elections in North Tapanuli district, ASN involvement in practical politics continues to be seen as providing support for the incumbent legislature to help with the campaign, help with the successful team, and to abuse the territory car. In addition, the cost of asn's involvement in North Tapanuli's politics in practical politics in the 2019 Legislative Elections is mutually beneficial between ASN and the Incumbent Legislature and newcomer, that motivation gains personal advantage and the lack of integrity to square as neutral.